IMPLEMENTASI METODE WATERFALL PADA PERANCANGAN APLIKASI INVENTORY BARANG - Sari, Yuntari Purba; Wijaya, Khana; Ariansyah, Ariansyah (LPPM UNIVERSITAS BINA INSAN, 2025)
Patrakom have a representative Base-base almost throughout Indonesia, where each Base has inventory. As Base Patrakom Prabumulih that they keep records of goods using a simple system that is recorded into a book and then transferred to MS EXCEL. Therefore, the amount of time required for the process of data collection items are also frequent errors and delays in making the report. Based on these problems, the required application in the processing of inventory items and reports are computerized so that the recording of the flow of goods in and out can be a rapid, precise and accurate. In this study, the method of collecting data through observation and study of literature. Applications compiled with the development stage procedure that includes needs analysis, data flow diagrams, implementation using PHP as the programming language and MySQL as the database. From research conducted, produced a system software design a web-based inventory with the ability to save data inventory of goods, goods mutation data and reports. The results of the research and manufacture of this program is expected to accelerate in data processing and delivery of reports to the Project Manager.